Case study of limits in computer employment in basic education (Research, Society and Development, 2019)
We live in times of much information considered to be liquid times by Bauman. In Basic Education schools, in general, there is the use of computation in the teaching and learning processes, but the Digital Information and Communication Technologies (TDIC) are not always used. This article aims to present a case study of the inappropriate use of resources of the TDIC by students of the ninth grade of basic education. A qualitative social research was carried out, such as a case study of the phenomenon of poor use of TDIC in a private school in the southeast region. It is observed that solving the problem involved the family successfully and improving the school's information security procedures.